Impact of coronavirus pandemic on mental health of children - Bagla, Jyoti; Rajan, Mahima; Maheshwari, Ananya; Chaudhry, Sangeeta; Dubey, Anand Prakash (Indian Journal of Child Health, 2021)
Background: The outbreak of coronavirus disease 2019 (COVID-19) pandemic has forced the children to stay indoors and minimize social interaction that has impacted their mental health. Aim: This study aims to assess the psychological impact of COVID-19 pandemic on children. Methods: This observational cross-sectional study was conducted in the Department of Pediatrics, ESIC PGIMSR, Basaidarapur, New Delhi, in the month of June 2020. Parents of children aged 6–17 years were asked to answer a questionnaire comprising questions from Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition scale and questions regarding COVID-19 pandemic which were structured by the authors. The data were analyzed using descriptive statistics. Results: Among the 150 responses, 57% were boys and 43% were girls with mean age of 11.62±3.5 years. The most common source of information about the pandemic was a family member (80%). About 99.7% of children were worried about getting infected. Inattention was the most common psychiatric symptom (49%), followed by mania (29%), anxiety (23%), and depression (23%). Predisposition to substance abuse and suicidal thoughts was majorly observed in adolescents. Conclusion: The pandemic is definitely causing psychosocial impact on children. The government and community need to be aware of such effects so that they can be dealt well in time.